â€œMatuya Mettaâ€ Creation of Javanese Dance Drama from the Story of Phra Lor - Oky Bima Reza Afrita (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
Matuya Metta is a Javanese dance-drama performance in the Yogyakarta dance style in the form of group choreography. This drama features the story of Phra Lor, famous in Thai literature. Matuya comes from the word â€œmatuâ€, meaning mother, and â€œmettaâ€ meaning love. So,